Welcome Home: Using persuasion to expand foreign fighter reintegration policies. - Harvey, Ruth E. (Tufts Archival Research Center, 2016)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: This paper analyzes the strategic and comprehensive use of persuasion tools used to shift political rhetoric regarding foreign fighter returnees, and through this case challenges the utility of ‘pure argumentative’ persuasion and the predictive power of persuasion presented in the literature.